Cosmológica, holista y relacional: una corriente de la religiosidad popular contemporánea = Cosmological, holistic and relational : a stream of contemporary popular religiosity - Semán, Pablo (Ciencias sociales y religión, 2001)
Considering that spaces of religious practices are crossed by particular symbolic logic, I will argue that in popular groups there is a flux of practices and representations which cross both religious denominations and autonomous practices. All of them are cosmological, holistic, and involve relationships - because they assert, at the same time, a continuum of experiences that modernist ideology divides into clusters, and the subject participation, characterized by the importance of the whole and its part character.